Pelatihan pembuatan Tes DaF dalam keterampilan membaca (lesen) dan menulis (schreiben) Bahasa Jerman bagi guru anggota IGBJI Cabang Makassar - Wahyu Kurniati Asri; Ambo Dalle; Abd. Kasim Achmad (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Community service Activities (PKM) aims to increase the knowledge of German teachers who belong to the Indonesian Teachers Association of Indonesia (IGBJI) Makassar branch in making a test of Deutsch-als Fremdsprachen ( DaF) on reading skills (Leseverstehen) and writing (Schreibfertigkeiten) in German. Problem: (1) Teachers have not been able to make Deutsch als test Fremdsprachen (DaF) in the skills of Reading (Leseverstehen) German language, (2) teachers have not been able to make a test of Deutsch-als Fremdsprachen (DaF) in writing skills (Schreibfertigkeit) German, (3) facilitators who can direct problems in the process of making a test of Deutsch als Femdsprachen (DaF) in the skills of Reading (license) and writing skills (Schreiben) in German are still limited. The methods used are: counseling, training, simulation, and discussion. The results are (1) Partner teachers have had the ability to make Deutsch-als test Fremdsprachen (DaF) in German-reading skills; (2) Partner teachers have had the ability to make Deutsch-als test Fremdsprachen (DaF) in German language writing skills.; (3) Partner teachers who have participated in training or counseling can be facilitators for other German language teachers who have not yet participated in the counseling. The implementation of the preparation of the training of Deutsch tests Fremdsprachen (DaF) in the skills of Reading (license) and writing skills (Schreiben) in the German language is held according to the planned and results achieved on the program activities. This community partnership can be categorized adequately because the activities of devotion to the community are categorized more than adequate (85%). This is the evident from the active of the teachers following the presentation of the material and in general they are very motivated and enthusiastic during the training activities.